Fusarium abutilonis and F. guadeloupense, two novel species in the Fusarium buharicum clade supported by multilocus molecular phylogenetic analyses. (4th July 2022) - O'Donnell, Kerry; Gräfenhan, Tom; Laraba, Imane; Busman, Mark; Proctor, Robert H.; Kim, Hye-Seon; Wiederhold, Nathan P.; Geiser, David M.; Seifert, Keith A.
ABSTRACT: This study was conducted to elucidate evolutionary relationships and species diversity within the Fusarium buharicum species complex (FBSC). We also evaluate the potential of these species to produce mycotoxins and other bioactive secondary metabolites. Maximum likelihood and maximum parsimony analyses of sequences from portions of four marker loci (ITS rDNA, TEF1, RPB1, and RPB2 ) and the combined 4495 bp data set support recognition of seven genealogically exclusive species within the FBSC. Two of the three newly discovered species are formally described as F. abutilonis and F. guadeloupense based on concordance of gene genealogies and morphological data. Fusarium abutilonis induces leaf, stem, and root lesions on several weedy Malvaceae ( Abution theophrasti, Anoda cristata, Sida spinosa ) and a fabaceous host ( Senna obtusifolia ) in North America and also was recovered from soil in New Caledonia. Fusarium abutilonis, together with its unnamed sister, Fusarium sp. ex common marsh mallow ( Hibiscus moscheutos ) from Washington state, and F. buharicum pathogenic to cotton and kenaf in Russia and Iran, respectively, were strongly supported as a clade of malvaceous pathogens. The four other species of the FBSC are not known to be phytopathogenic; however, F. guadeloupense was isolated from human blood in Texas and soil in Guadeloupe. The former isolate is unique because it represents the only known case of a fusarial infection disseminated hematogenously by a species lacking microconidia and the only documented fusariosis caused by a member of the FBSC. Whole genome sequence data and extracts of cracked maize kernel cultures were analyzed to assess the potential of FBSC isolates to produce mycotoxins, pigments, and phytohormones.